Internalisasi Nilai-Nilai Moderasi Beragama di Kalangan Mahasantri - Anwar, Khoirul; Rosid, Abdur (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
Islamic boarding schools are the center of civilization in Indonesia which provide deep religious understanding to the students, specifically an understanding of religious moderation also needs to be given to the students as an effort to prevent religious conflict by internalizing the values ​​of moderation to help the students become better and more balanced, as well as more tolerant and respectful of other people's differences in religion and beliefs. Referring to several problems that occur among students, researchers feel it is important to carry out religious moderation-based service in the city of Malang, especially at the Sabilurrosyad Islamic boarding school. This Islamic boarding school consists of heterogeneous students, they come from various general and Islamic campuses in the city of Malang. In this service, the main method used is the seminar method and focus group discussion and five stages of internalization are carried out, namely the stage of recognizing values, accepting values, practicing values, internalizing values ​​and strengthening values. The results of the research are 1) Value Introduction Stage, 2) Value Acceptance Stage which consists of Personal Reflection, Personal Experience and Social Acceptance. 3) Moderation Values ​​Practice Stage 4) Values ​​Internalization Stage which includes Understanding Moderation Values, Reflection and Self-Evaluation, Habit Formation and Consistency and Commitment 5) Values ​​Strengthening Stage which includes Reintroduction of Moderation Values, Education and Learning, Direct Experience, Reflection Self and Strengthening and Appreciating the Values ​​of Moderation.